EFFECT OF BLANCHING AND DRYING METHODS ON PHYSICOCHEMICAL PROPERTIES OF ORANGE SWEET POTATO FLOUR (Ipomoea batatas L.) - Zulman Efendi; Fitri Electrika D. Surawan; Winarto Winarto (BPFP Faperta UNIB, 2015)
Orange sweet potato is one of many tubers as raw materials for food processing diversify. However, problems in flour processing such as color change, degradation of the material, especially in the use of 100oC for a long time blanching. This study aims to find the physicochemical properties of orange sweet potato flour. The study was conducted with a CRD by factorial. The first factor were without blanching, blanching 60°C, and 80°C, while the second factor were sun and oven drying. The results showed that value of yield from 28.69% up to 21.23%, but bulk density from 0.55 up to 0.70, water absorption index from 0.20 up to 0.64 (w/w), significantly. Meanwhile, water content and water solubility index in the range 4.99-7.40% and 0.022-0.064 (w/v), not significantly. L value has decreased until 65.87 while the value of a and b have increased with increasing of blanching temperature and drying oven method, significantly. a+ and b+ value were in the range of 9.47 to 11.13 and from 21.60 to 28.67. Effect of blanching 80oC and drying oven method have proved to be better production of orange sweet potato flour